(untitled) (Journal of the College of Basic Education, 2023)
The problem of the current research is directed towards the weakness in the professional performance of many male and female teachers in middle and preparatory schools.This weakness is due, among other reasons, to the poor vocational preparation of the student / teacher in the colleges of education, as this aspect of the preparation suffers from weakness in the applied aspect, due to several reasons, including the absence of applied and experimental schools attached to the college, or the absence of workshops or laboratories for education. Micro and modern technological means.It is no secret that the importance of the teacher is the basis for every learning process, this process that cannot bear fruit unless the basis for it is well prepared.And when the preparation of schools is mentioned, it certainly means scientific and vocational preparation, that preparation based on the actual integration between them, since the school preparation curricula should work in both parts to provide schools with the skills, experiences and attitudes that make them able to practice the teaching profession, and raise their level of performance and motivate them to creativity and innovation. With the necessity of introducing them also to the modern methods and methods of teaching, introducing them to the proposed solutions to the problems of education, and developing their national and social sense.